Determinants of Bankruptcy Banking after the Global Financial Crisis (GFC): Theoritical Review - Asfahan Amir Ishak; Abdul Mongid (IPTEK Journal of Proceedings Series, 2020)
The failure of some financial institutions can cause other banks to go bankrupt, and ultimately cause damage to the financial system throughout the world. Bankrupt is a condition in which a company suffers from a lack of funds to run its business. The paper is conceptual and the design of this research is qualitative method based on a theoretical review from many kinds of literature and previous researches related to this concept. There are two basic theories about (1) signaling theory for providing better information and positive signals about the company, as well as negative signals to and (2) the margin pressure theory for measuring about the risk of negative effects from internal or external forces on a company's profitability margins. This study aimed to determine the significant contribution of internal factors such as size, equity to total asset, loan to asset ratio, cost to income ratio, loan loss reserves, and from external factors such as gross domestic product growth, and inflation in predicting bankruptcy bank after the Global Financial Crisis. The researcher believes that the proposition of this study results can be tested empirically mainly in the banking industry